2006
DOI: 10.1093/jn/136.1.123
|View full text |Cite
|
Sign up to set email alerts
|

Bread Fortified with Cholecalciferol Increases the Serum 25-HydroxyvitaminD Concentration in Women as Effectively as a Cholecalciferol Supplement

Abstract: Fortification of foods is a feasible way of preventing low vitamin D status. Bread could be a suitable vehicle for fortification because it is a common part of diets worldwide. The bioavailability of cholecalciferol from bread is not known. We studied cholecalciferol stability, the concentration of the added cholecalciferol, the dispersion of cholecalciferol in bread, and the bioavailability of cholecalciferol from fortified bread. Three batches of fortified low-fiber wheat and high-fiber rye breads were baked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
101
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(105 citation statements)
references
References 22 publications
3
101
0
1
Order By: Relevance
“…Such a delay, made many others to do the same researches. Even well after 2008 many papers were published concerning the same issue and all emphasized on the importance of the consequences (23,(28)(29)(30)(32)(33)(34) (50) and bread (51).…”
Section: Discussionmentioning
confidence: 99%
“…Such a delay, made many others to do the same researches. Even well after 2008 many papers were published concerning the same issue and all emphasized on the importance of the consequences (23,(28)(29)(30)(32)(33)(34) (50) and bread (51).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D 3 deficiency is known as a major hidden health problem worldwide. In addition to the typical and sever complications of vitamin D 3 deficiency, like rickets in children, osteomalacia and osteoporosis in adults, inadequate serum concentrations of this vitamin may induce long lasting negative effects.…”
Section: Introductionmentioning
confidence: 99%
“…(1) Food fortification is a commonly accepted approach for preventing low vitamin D 3 status. Although animal originated foods are commonly considered as a suitable vehicle for vitamin D 3 fortification, bread has also been considered for this purpose in the recent years (1)(2)(3) . Being a staple food item and available to all social classes, vitamin D 3 fortified bread maybe more efficient for delivering this vitamin in to the low income individuals diet, (3) specifically in developing countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dose, latitude and baseline 25(OH)D were identified a priori as probable sources of heterogeneity. Fourteen trials were included (n 936; 483 treated and 453 controls), derived from eleven published studies (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) , all of which showed a statistically significant beneficial effect of food fortification on circulating 25(OH)D concentrations. Individual treatment effects ranged from 10.00 (95% 23.20) to 36.25 (22.47, 50.03) nmol/l.…”
mentioning
confidence: 99%